2006
DOI: 10.1038/sj.hdy.6800863
|View full text |Cite
|
Sign up to set email alerts
|

Wing dimorphism in aphids

Abstract: Many species of insects display dispersing and nondispersing morphs. Among these, aphids are one of the best examples of taxa that have evolved specialized morphs for dispersal versus reproduction. The dispersing morphs typically possess a full set of wings as well as a sensory and reproductive physiology that is adapted to flight and reproducing in a new location. In contrast, the nondispersing morphs are wingless and show adaptations to maximize fecundity. In this review, we provide an overview of the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
324
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(346 citation statements)
references
References 85 publications
(109 reference statements)
7
324
1
6
Order By: Relevance
“…Wing morphology displays phenotypic plasticity in response to several environmental variables including rearing density, a likely correlate with acquisition, with different species displaying very different responses. In aphids and planthoppers, induction of flight capable morphs increases in response to crowding and low nutrition [28,29], while in crickets, group rearing and other stressors increase induction of flightless morphs [30,31]. Both of these examples, the lifespan-reproduction trade-off and the flight capability-reproduction trade-off, demonstrate the wide variation in allocation patterns across different species.…”
Section: The Central Importance Of the Interplay Between Resource Acqmentioning
confidence: 99%
“…Wing morphology displays phenotypic plasticity in response to several environmental variables including rearing density, a likely correlate with acquisition, with different species displaying very different responses. In aphids and planthoppers, induction of flight capable morphs increases in response to crowding and low nutrition [28,29], while in crickets, group rearing and other stressors increase induction of flightless morphs [30,31]. Both of these examples, the lifespan-reproduction trade-off and the flight capability-reproduction trade-off, demonstrate the wide variation in allocation patterns across different species.…”
Section: The Central Importance Of the Interplay Between Resource Acqmentioning
confidence: 99%
“…It is noteworthy that the molecular genetics underlying wing plasticity in planthoppers cannot fully account for the proximate causes of wing polymorphism in other insect species. For example, with regard to aphid species, they have complex life cycles showing cyclic parthenogenesis with alternating asexual and sexual generations, which has been intensively studied and reviewed elsewhere [2,3,[55][56][57]. Instead of the short-and long-winged morphs, wingless and winged morphs were produced in most aphid species.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Currently, the effect of environmental factors on BPH wing dimorphism is controversial. As with many reports on aphids and crickets [1,2,[27][28][29][30], the level of juvenile hormones (JH) has long been thought to control wing-morph switch in planthoppers. Topical application of JHs or JH agonists on the BPHs at sensitive developmental stages induced short-winged morphs [20,31], whereas treatment with JH antagonists induced long-winged morphs [32][33][34].…”
Section: Environmental Factors Influencing Wing Dimorphism In the Bromentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the streamdwelling water strider (Aquarius remigis) Fairbairn and King (2009) have shown that the frequency of macropterous individuals usually increases with temperature, a likely cue of habitat drying. Crowding is also a common factor that increases production of macropterous individuals in many insects (for example, Braendle et al, 2006;Poniatowski and Fartmann, 2009).…”
Section: Introductionmentioning
confidence: 99%